(untitled) (Bangladesh Journal of Agricultural Research, 2018)
The aim of this study was to isolate superior inbred lines and better combining parents for suitable hybrids and to determine percent of heterosis using standard commercial checks in a 7 × 7 diallel analysis excluding reciprocals over five environments. The mean sum of square obtained from combined analysis of variance showed the presence of genetic variability among the crosses, environment and crosses × environment interaction for all of the characters under study. The variances for general combining ability (GCA) and specific combining ability (SCA) of variance were found significant for all the characters. However, relative magnitude of variances indicated that additive gene effects were more prominent for all the characters studied. GCA and SCA effects both showed significant interaction with environment for all the traits. This clearly suggested the need of selecting different parental lines for hybrids for different ecological situations. Parents P3, P5 and P6 were the best general combiner for high yield; parents P6 for earliness; and P1, P2 and P3 for dwarf plant type. The range of heterosis expressed by different crosses was from -13.04 to 5.25 % percent for grain yield. The better performing six crosses (P1 × P2, P1 × P5, P3 × P4, P3 × P6, P3 × P7 and P4 × P5) can be utilized for developing high yielding hybrid varieties as well as for exploiting hybrid vigour. These crosses also need to be evaluated further in multilocations. Bangladesh J. Agril. Res. 43(1): 125-134, March 2018